Genetic Factors and Their Role in the Pathogenesis of Biliary Atresia - Wu, Li-Na; Zhu, Zhi-Jun; Sun, Li-Ying (Frontiers in Pediatrics, 2022)
Biliary Atresia, a common basis for neonatal cholestasis and primary indication for Liver Transplantation, accounts for 60% of pediatric Liver Transplantations. While the pathogenesis of Biliary Atresia remains obscure, abnormalities within bile ducts and the liver, inflammation, fibrosis and cilia defects are thought to comprise the pathological basis for this condition. The findings of genetic variants in Biliary Atresia, such as Copy Number Variations and Single Nucleotide Polymorphism, are considered as essential factors in the development of this condition. In this review, we summarize and analyze these Biliary Atresia variants from a perspective of their pathological characteristics. In conclusion, such analyses may offer novel insights into the pathogenesis of Biliary Atresia and provide a foundation for future studies directed toward a better understanding and treatment of Biliary Atresia.